Case-Based Learning In Improving Critical Thinking Skill On Reading Comprehension for The Eleventh Grade Students at SMA N 2 Semarang - Aisy Ghina Rihadatul; Nani Hidayati (Jurnal Ilmiah Sultan Agung, 2022)
The aim of this study was to find out whether the use of CBL is effective in improving students' critical thinking skill of the eleventh grade students of SMA N 2 Semarang in academic year of 2021/2022. The design of this study was quasi experimental design and the method that was quantitative method. The sample of this study consisted of 36 students of XI MIPA 3 as the experimental class and 36 students of XI MIPA 4 as the control class. The try out test to XI MIPA 1 was done to know the validity and the reliability of the instrument. Pre-test and post-test was given to the experimental and control class. The result was analyzed by using SPSS 26 version. The result of the pre-test of experimental and control class were 64.17 and 57.89. While the result of post-test of experimental and control class were 75.11 and 72.22. The post-test result from both classes were analyzed by using t-test. The result of the analysis shows that sig (2-tailed) 0.333 ≥ 0.05 which means there was no significant difference in students’ mean reading scores between experimental class which was taught by using CBL and control class which was not taught by using CBL. It was concluded that H1 was rejected and H0 was accepted. Therefore, the use of case-based learning in improving critical thinking skill on reading comprehension for the eleventh grade students at SMA N 2 Semarang was not effective.